(3GdYdGeGJ GdJLGQjI hWfjG hOhdjGs - (3UdGM(B, (3Rjf GdOjfs ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2005)
(3GdJWhQ GdJGQjNj hGdJTQjYj ddYdGeI GdJLGQjI hGdJYQja HgG,JejjR GdYdGeI GdJLGQjI Yf ZjQgG hCSS GNJjGQgG hNUGFUgG,GdTQhW GdehVhYjI hGdTcdjI ddYdGeI GdJLGQjI hBKGQ JSLjdgG,JSLjd GdYdGeI GdJLGQjI GdCLfHjI hMeGjJgG,GdMb aj GdYdGeI GdJLGQjI,GdMeGjI GdbGfhfjI ddYdGeI GdJLGQjI,GdJfXje GdOhdj ddYdGeI GdJLGQjIs
(3GdedGMb(B:(3U(B.347-450(3;HHdjhZQGajG(B:(3U(B.451-456s
Keywords: (3GdYdGeGJ GdJLGQjIs; (3GdbGfhf GdJLGQjs